Supercritical water gasification of high-salinity oily wastewater: study on inorganic salt deposition behavior and mechanisms - Siqi Rong; Hanbing Jia; Kun Jiang; Libo Lu; Zhiyong Peng; Jialing Xu; Hui Jin; Liejin Guo (Fuel, 2026)

Characterization and Expression Analysis of KCS Genes in Cotton: Insights Into Temperature-Regulated Fuzz Development - Yuchen Song; Langjing Hua; Yanan Xu; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Plant Molecular Biology Reporter, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Optimizing inlet design for improved water renewal and solids removal in circular tanks in recirculating aquaculture systems - Huacheng Li; Qiushi Yang; Wenhan Li; Chengchen Jiang; Tingting Xu; Yutian Yuan; Rong Tang; Li Li; Yale Deng; Dapeng Li (Aquacultural Engineering, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Evaluation of acute neurotoxic effects induced by Gelsemium elegans in rats - Meng-Ting Zuo; Jiang-Yu Long; Chong-Yin Huang; Yi-Rong Wang; Xiao-Qing Xu; Zhao-Ying Liu (Toxicological Research, 2026)

Deciphering the multivariable interactions of MOFs in heavy metal adsorption via explainable machine learning for sustainable and resource-efficient adsorbent development - Mingxing Jiang; Weiwei Fu; Xiaoliang Zhao; Rong Gao; Duanping Xu; Sitan Wang (Journal of Cleaner Production, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

A nitrogen-rich covalent organic framework with high conductivity for high specific capacity Li-ion battery cathode - Xiaoning Zhan; Yucheng Jin; Rong Jiang; Dongdong Qi; Xiya Yang; Qi Zhang; Qingmei Xu; Zhixin Liu; Liancong Yue; Hailong Wang (Science Bulletin, 2026)

Assessing green synergy efficiency to advance sustainable development goals: A multi-objective collaborative efficiency analysis framework - Xiaomei Shen; Rong Yan; Xiangqin Xu; Huiwen Fang; Mingdong Jiang (Journal of Cleaner Production, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Interfacial adsorption mechanism of xanthan gum pre-assembled with calcium ions as an efficient depressant for Cu-S flotation separation under low-alkaline - Hulin Gao; Jian Liu; Jiamei Hao; Meiguang Jiang; Xu Bai; Da Li; Rong Huang (Minerals Engineering, 2026)

Synergistic transformation of alkylbisphenols (BPA, BPE, and BPF) mediated by ammonia-oxidizing bacteria and heterotrophic bacteria in nitrifying activated sludge - Hang Xu; Wenhui Zhang; Sicheng Zhu; Bingyu Shen; Xinyu Li; Bingqi Jiang; Lianhong Wang; Philippe F.X. Corvini; Max M. Häggblom; Rong Ji (Journal of Hazardous Materials, 2026)

Longifolene and β-ionone promote astaxanthin accumulation in Microcystis aeruginosa by serving signaling function - Lexin Huang; Fei Jiang; Shanshan Song; Xinyuan Zhao; Zhehan Yang; Junjie Ma; Haozhe Xu; Rong Hu; Tianyu Huang; Zhijie Chen; Huiying Fu; Zhaojiang Zuo (Algal Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Kinetic model reveals microbial-mediated hydrogen consumption and abiotic mineral reactions jointly control hydrogen depletion during geological storage - Dongfang Ke; Weiqiang Feng; Peng Liao; Rong Li; Ruina Xu; Yu-Min Chou; Peixue Jiang (Applied Geochemistry, 2026)

A fungal polysaccharide from Trametes orientalis: Structural elucidation and multifaceted antitumor mechanisms via metastasis, angiogenesis, and immunomodulation - Wenrui He; Haojing Jiang; Mingming Rong; Xinxing Li; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Spatio-temporal variations in the supply and demand of ecosystem services with multi-scenario prediction in Guangzhou City, China - Jun Wu; Zhi-Yun Jiang; Yan-Yu Xu; Lin Lin; Rong Guo; Yi-Jia Wang (Environmental Science and Pollution Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

Megastigmane glycosides from Heterosmilax yunnanensis and their neuroprotective activity - Rong-Rong Du; Wen-Jie Qin; Xiu-Mei Duan; Xu Zhang; Ya-Nan Yang; Jian-Shuang Jiang; Xiang Yuan; Pei-Cheng Zhang (Phytochemistry, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Advancing treatment strategies against MRSA: unveiling the potency of tubuloside A in targeting sortase A and mitigating pathogenicity - Yangming Xu; Yanhe Luan; Rong Wang; Zhengjie Su; Li Wang; Yinghui Liu; Guangzhi Jiang; Bingmei Wang (World Journal of Microbiology and Biotechnology, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

Experimental study of interception effect by submerged dam on microplastics - Jianhao Jiang; Lulu He; Junping Liu; Xu Liu; Junbao Huang; Li Rong (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Sensing host and environmental cues by fungal GPCRs - Cong Jiang; Aliang Xia; Daiying Xu; Jin-Rong Xu (Current Opinion in Plant Biology, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Basic study on cryopreservation of rat calvarial osteoblasts with different cryoprotectants - Xu Jiang; Tan Zhijian; Cao Min; Yu Rong; Tan Xinghui; Xin Gong (Cell and Tissue Banking, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Phosphoric acid pre-swelling strategy constructing acid-doped fluoropoly(aryl pyridinium) membranes to enable high-performance vanadium flow batteries - Tao Ban; Zihui Wang; Yinfei Wang; Yifei Xu; Zhanpeng Jiang; Rong Zeng; Xiuling Zhu (Chemical Engineering Journal, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Profiling of fungal communities in functional food Cistanches herba using high–throughput sequencing - Chune Fan; Rong Xu; Mengyue Guo; Wenjun Jiang; Meihua Yang; Yujie Dao; Xiaohui Pang (Food Bioscience, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

Dual-edged sword effects of sulfation/hydration on Ce-doped TiO2(001) single-atom catalyst for NH3-SCR reaction: A first-principles study - Ye Jiang; Yichao Xu; Xin Sun; Guomeng Zhang; Zihan Rong; Yinsheng Jiang; Jiayao Song; Zhengda Yang (Fuel, 2024)

Efficient recovery of copper resources from copper smelting waste acid based on Cu(Ⅱ)/As(Ⅲ) competitive sulfuration mechanism - Xiaolu Sun; Linhua Jiang; Ning Duan; Guangbin Zhu; Yanli Xu; Hao Jin; Yong Liu; Rong Zhang (Journal of Cleaner Production, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Effect of blending ratio on the compatibility and stability of konjac glucomannan/starch composite systems - Qian Zhang; Sicong Yan; Rong Zhou; Xu Yan; Peineng Zhu; Lingyun Chen; Fatang Jiang (Food Hydrocolloids, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Separated two-stage hydrothermal liquefaction of livestock manure for high-quality bio-oil with low-nitrogen content: Insights on nitrogen migration and evolution - Siyuan Long; Haiwei Jiang; Jinming Shi; Xianbin Ai; Zhigang Que; Hanbing Nie; Chunbao Charles Xu; Rong Huang; Yinxuan Fu; Weiran Yang (Chemical Engineering Journal, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Echinacoside, a promising sortase A inhibitor, combined with vancomycin against murine models of MRSA-induced pneumonia - Tao Jiang; Dai Yuan; Rong Wang; Chunhui Zhao; Yangming Xu; Yinghui Liu; Wu Song; Xin Su; Bingmei Wang (Medical Microbiology and Immunology, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

A cascade electro-dehydration process for simultaneous extraction and enrichment of uranium from simulated seawater - Ruirui Li; Huangying Wang; Junying Yan; Rong Fu; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Water Research, 2023)

A direct electrochemical substitution electrodialytic system for CO2 conversion into high value-added soda - Huangying Wang; Haiyang Yan; Kang Peng; Junying Yan; Rong Fu; Ruirui Li; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Amycolatolides A and B: Two new secondary metabolites from the lichen-derived actinomycete Amycolatopsis sp. YIM 130923 - Qing-Rong Yang; Yi Jiang; Chuan-Sheng Liu; Tang-Chang Xu; Rong Huang; Shao-Hua Wu (Phytochemistry Letters, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Microwave discharge for rapid introduction of bimetallic-synergistic configuration to conductive catecholate toward long-term supercapacitor - Huiyu Jiang; Jinglin Xian; Rong Hu; Shiyun Mi; Liyun Wei; Guangyu Fang; Zhiao Wu; Siqi Xu; Mingzhao Fan; Kaisi Liu; Huimin Yu; Weilin Xu; et al. (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

Damage Evaluation and Statistic Constitutive Model of High-Temperature Granites Subjected to Liquid Nitrogen Cold Shock - Zhiheng Chen; Song Sha; Lida Xu; Junsong Quan; Guan Rong; Maiyong Jiang (Rock Mechanics and Rock Engineering, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Detection of functional and structural brain alterations in female schizophrenia using elastic net logistic regression - Ying Wu; Ping Ren; Rong Chen; Hong Xu; Jianxing Xu; Lin Zeng; Donghui Wu; Wentao Jiang; NianSheng Tang; Xia Liu (Brain Imaging and Behavior, 2022)
Neuroimaging technique is a powerful tool to characterize the abnormality of brain networks in schizophrenia. However, the neurophysiological substrate of schizophrenia is still unclear. Here we investigated the patterns of brain functional and structural changes in female patients with schizophrenia using elastic net logistic regression analysis of resting-state functional magnetic resonance imaging data. Data from 52 participants (25 female schizophrenia patients and 27 healthy controls) were obtained. Using an elastic net penalty, the brain regions most relevant to schizophrenia pathology were defined in the models using the amplitude of low-frequency fluctuations (ALFF) and gray matter, respectively. The receiver operating characteristic analysis showed reliable classification accuracy with 85.7% in ALFF analysis, and 77.1% in gray matter analysis. Notably, our results showed eight common regions between the ALFF and gray matter analyses, including the Frontal-Inf-Orb-R, Rolandic-Oper-R, Olfactory-R, Angular-L, Precuneus-L, Precuenus-R, Heschl-L, and Temporal-Pole-Mid-R. In addition, the severity of symptoms was found positively associated with the ALFF within the Rolandic-Oper-R and Frontal-Inf-Orb-R. Our findings indicated that elastic net logistic regression could be a useful tool to identify the characteristics of schizophrenia -related brain deterioration, which provides novel insights into schizophrenia diagnosis and prediction.

Inclusion of Ecological Water Requirements in Optimization of Water Resource Allocation Under Changing Climatic Conditions - Wencong Yue; Zhongqi Liu; Meirong Su; Meng Xu; Qiangqiang Rong; Chao Xu; Zhenkun Tan; Xuming Jiang; Zhixin Su; Yanpeng Cai (Water Resources Management, 2022)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Consuming Different Structural Parts of Bamboo Induce Gut Microbiome Changes in Captive Giant Pandas - Zheng Yan; Qin Xu; Walter H. Hsu; Stephan Schmitz Esser; James Ayala; Rong Hou; Ying Yao; Dandan Jiang; Shibin Yuan; Hairui Wang (Current Microbiology, 2021)
Giant pandas consume different structural parts of bamboo (shoots, leaves and culms) during different seasons. Previous research showed different bamboo parts have varying nutritional content and that a long-term diet consisting of a single part of bamboo resulted in remarkable metabolic changes within captive giant pandas. However, the effects on the gut microbiome of giant pandas, as a result of a single bamboo part diet, have not been investigated. Here, we evaluated the changes in gut microbial communities based on single bamboo part diets and their potential implications by using 16S rRNA gene-based amplicon sequencing and metagenome shotgun sequencing. We found that the composition and function of the gut microbiome from captive giant pandas fed exclusively culms were significantly different from that of individuals fed shoots or leaves. During the culm feeding period, the gut microbiome showed strongest digestive capabilities for cellulose, hemicellulose and starch, and had the highest potential abilities for the biosynthesis of bile acids, fatty acids and amino acids. This suggests the microbiome aids in breaking down culm, which is more difficult for giant pandas to digest, as a means to compensate for the nutrient poor content of the culm. Genes related to fatty acid metabolism and tricarboxylic acid cycle enzymes were more abundant during the leaf stage diet than that in the shoot and culm stages. Thus, the microbiome may help giant pandas, which typically have low lipase levels, with fat digestion. These results illustrate that adaptive changes in the gut microbiome community and function may be an important mechanism to aid giant panda digestion when consuming different structural parts of bamboo.

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Symbiotic fungi undergo a taxonomic and functional bottleneck during orchid seeds germination: a case study on Dendrobium moniliforme - Yuan-Yuan Meng; Xu-Li Fan; Lv-Rong Zhou; Shi-Cheng Shao; Qiang Liu; Marc-André Selosse; Jiang-Yun Gao (Symbiosis, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Independent losses and duplications of autophagy‐related genes in fungal tree of life - Qinhu Wang; Huiquan Liu; Huaijian Xu; Ruonan Hei; Shijie Zhang; Cong Jiang; Jin‐Rong Xu (Environmental Microbiology, 2019)
Summary Autophagy is important for growth, development and pathogenesis in fungi. Although autophagic process is generally considered to be conserved, the conservation and evolution of ATG genes at kingdom‐wide remains to be conducted. Here we systematically identified 41 known ATG genes in 331 species and analyzed their distribution across the fungal kingdom. In general, only 20 ATG genes are highly conserved, including most but not all the yeast core‐autophagy‐machinery genes. Four functional protein groups involved in autophagosome formation had conserved and non‐conserved components, suggesting plasticity in autophagosome formation in fungi. All or majority of the key ATG genes were lost in several fungal groups with unique lifestyles and niches, such as Microsporidia, Pneumocystis and Malassezia . Moreover, majority of ATG genes had A‐to‐I RNA editing during sexual reproduction in two ascomycetes and deletion of FgATG11 , the ATG gene with the most editing sites in Fusarium affected ascospore releasing. Duplication and divergence also was observed to several core ATG genes, such as highly divergent ATG8 paralogs in dermatophytes and multiple ATG15 duplications in mushrooms. Taken together, independent losses and duplications of ATG genes have occurred throughout the fungal kingdom and variations in autophagy exist among different lineages and possibly different developmental stages.

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Strategies to Determine Assay Format for the Assessment of Neutralizing Antibody Responses to Biotherapeutics - Bonnie Wu; Shan Chung; Xu-Rong Jiang; Jim McNally; Joao Pedras-Vasconcelos; Renuka Pillutla; Joleen T. White; Yuanxin Xu; Shalini Gupta (The AAPS Journal, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Thioredoxins are involved in the activation of the PMK1 MAP kinase pathway during appressorium penetration and invasive growth in Magnaporthe oryzae - Shijie Zhang; Cong Jiang; Qiang Zhang; Linlu Qi; Chaohui Li; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary In Magnaporthe oryzae , the Mst11‐Mst7‐Pmk1 MAP kinase pathway is essential for appressorium formation and invasive growth. To determine their roles in Pmk1 activation and plant infection, we characterized the two thioredoxin genes, TRX1 and TRX2 , in M. oryzae . Whereas the Δ trx1 mutants had no detectable phenotypes, deletion of TRX2 caused pleiotropic defects in growth, conidiation, light sensing, responses to stresses and plant infection progresses. The Δ trx1 Δ trx2 double mutant had more severe defects than the Δ trx2 mutant and was non‐pathogenic in infection assays. The Δ trx2 and Δ trx1 Δ trx2 mutant rarely formed appressoria on hyphal tips and were defective in invasive growth after penetration. Pmk1 phosphorylation was barely detectable in the Δ trx2 and Δ trx1 Δ trx2 mutants. Deletion of TRX2 affected proper folding or intra‐/inter‐molecular interaction of Mst7 and expression of the dominant active MST7 allele partially rescued the defects of the Δ trx1 Δ trx2 mutant. Furthermore, Cys305 is important for Mst7 function and Trx2 directly interacts with Mst7 in co‐IP assays. Our data indicated that thioredoxins play important roles in intra‐cellular ROS signalling and pathogenesis in M. oryzae . As the predominant thioredoxin gene, TRX2 may regulate the activation of Pmk1 MAPK via its effects on Mst7.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Preferable procedure for the screening of syphilis in clinical laboratories in China - Ke-Di Wang; Dong-Jiang Xu; Jian-Rong Su (Infectious Diseases, 2016)

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity - Yuling Wu; Jia J. Li; Hyun Jun Kim; Xu Liu; Weiyi Liu; Ahmad Akhgar; Michael A. Bowen; Susan Spitz; Xu-Rong Jiang; Lorin K. Roskos; Wendy I. White (The AAPS Journal, 2015)

High precision in-situ Pb isotopic analysis of sulfide minerals by femtosecond laser ablation multi-collector inductively coupled plasma mass spectrometry - HongLin Yuan; Cong Yin; Xu Liu; KaiYun Chen; ZhiAn Bao; ChunLei Zong; MenNing Dai; ShaoCong Lai; Rong Wang; ShaoYong Jiang (Science China Earth Sciences, 2015)

Activation of the signalling mucin MoM sb2 and its functional relationship with C bp1 in M agnaporthe oryzae - Guanghui Wang; Guotian Li; Shijie Zhang; Cong Jiang; Jun Qin; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Various surface signals are recognized by M agnaporthe oryzae to activate the P mk1 MAP kinase that is essential for appressorium formation and invasive growth. One of upstream sensors of the P mk1 pathway is the MoM sb2 signalling mucin. However, the activation of MoM sb2 and its relationship with other sensors is not clear. In this study, we showed that the cleavage and transmembrane domains are essential for MoM sb2 functions. Cleavage of MoM sb2 was further confirmed by western blot analysis, and five putative cleavage sites were functionally characterized. Expression of the extracellular region alone partially rescued the defects of M omsb2 in appressorium formation and virulence. The cytoplasmic region of MoM sb2, although dispensable for appressorium formation, was more important for penetration and invasive growth. Interestingly, the M omsb2 cbp1 double mutant deleted of both mucin genes was blocked in P mk1 activation. It failed to form appressoria on artificial surfaces and was non‐pathogenic. In addition, we showed that MoM sb2 interacts with R as2 but not with MoC dc42 in co‐immunoprecipitation assays. Overall, results from this study indicated that the extracellular and cytoplasmic regions of MoM sb2 have distinct functions in appressorium formation, penetration and invasive growth, and MoM sb2 has overlapping functions with C bp1 in recognizing environmental signals for P mk1 activation.

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

FgSKN 7 and FgATF 1 have overlapping functions in ascosporogenesis, pathogenesis and stress responses in F usarium graminearum - Cong Jiang; Shijie Zhang; Qiang Zhang; Yin Tao; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Fusarium head blight caused by F usarium graminearum is one of the most destructive diseases of wheat and barley. Deoxynivalenol ( DON ) produced by the pathogen is an important mycotoxins and virulence factor. Because oxidative burst is a common defense response and reactive oxygen species ( ROS ) induces DON production, in this study, we characterized functional relationships of three stress‐related transcription factor genes FgAP 1 , FgATF 1 and FgSKN 7. Although all of them played a role in tolerance to oxidative stress, deletion of FgAP 1 or FgATF 1 had no significant effect on DON production. In contrast, F gskn7 mutants were reduced in DON production and defective in H 2 O 2 ‐induced TRI gene expression. The F gap1 mutant had no detectable phenotype other than increased sensitivity to H 2 O 2 and F gap1 F gatf1 and F gap1 F gskn7 mutants lacked additional or more severe phenotypes than the single mutants. The F gatf1 , but not F gskn7 , mutant was significantly reduced in virulence and delayed in ascospore release. The F gskn7 F gatf1 double mutant had more severe defects in growth, conidiation and virulence than the F gatf1 or F gskn7 mutant. Instead of producing four‐celled ascospores, it formed eight small, single‐celled ascospores in each ascus. Therefore, FgSKN 7 and FgATF 1 must have overlapping functions in intracellular ROS signalling for growth, development and pathogenesis in F . graminearum .

The Effects of Fludarabine on Rat Cerebral Ischemia - Qian Xu; Chunjuan Jiang; Yutao Rong; Chun Yang; Ying Liu; Kai Xu (Journal of Molecular Neuroscience, 2015)

Mantle Transition Zone Structure Beneath Southeastern China and its Implications for Stagnant Slab and Water Transportation in the Mantle - Rong Huang; Yixian Xu; Yinhe Luo; Xiaohuan Jiang (Pure and Applied Geophysics, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

cDNA cloning and characterization of 5′ upstream promoter region of porcine mef2c gene - Min Liu; De Quan Xu; Jian Peng; Rong Zheng; Fenge Li; Si Wen Jiang (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)